Detrimental Effect of Broad-spectrum Antibiotics on Intestinal Microbiome Diversity in Patients After Allogeneic Stem Cell Transplantation: Lack of Commensal Sparing Antibiotics. (17th August 2018) - Weber, Daniela; Hiergeist, Andreas; Weber, Markus; Dettmer, Katja; Wolff, Daniel; Hahn, Joachim; Herr, Wolfgang; Gessner, André; Holler, Ernst
Abstract : Disruptions of the intestinal microbiome are involved in the pathophysiology of acute gastrointestinal graft versus host disease in patients after allogeneic stem cell transplantation. Systemic broad-spectrum antibiotics display a major risk factor for the loss of protective commensal gut bacteria. Abstract: Background: Maintaining gastrointestinal (GI) microbiome diversity plays a key role during allogeneic stem cell transplantation (ASCT), and loss of diversity correlates with acute GI graft versus host disease (GvHD) and poor outcomes. Methods: In this retrospective analysis of 161 ASCT patients, we used serial analyses of urinary 3-indoxyl sulfate (3-IS) levels and GI microbiome parameters within the first 10 days after ASCT to identify potential commensal microbiota–sparing antibiotics. Based on antibiotic activity, we formed 3 subgroups (Rifaximin without systemic antibiotics, Rifaximin with systemic antibiotics, and Ciprofloxacin/Metronidazole with/without systemic antibiotics). Results: Mono-antibiosis with Rifaximin revealed higher 3-IS levels ( P < .001), higher Clostridium cluster XIVa (CCXIVa) abundance ( P = .004), and higher Shannon indices ( P = .01) compared to Ciprofloxacin/Metronidazole with/without systemic antibiotics. Rifaximin followed by systemic antibiotics maintained microbiome diversity compared to Ciprofloxacin/Metronidazole with/without systemic antibiotics, as these patients showed still higher 3-IS levels ( P = .04), higher CCXIVa copy numbers ( P = .01), and higher Shannon indexes ( P = .01). Even for this larger cohort of patients, the outcome was superior with regard to GI GvHD ( P = .05) and lower transplant-related mortality ( P < .001) for patients receiving Rifaximin plus systemic antibiotics compared to other types of systemic antibiotic treatment. Antibiosis with Ciprofloxacin/Metronidazole (n = 12, P = .01), Piperacillin/Tazobactam (n = 52, P = .01), Meropenem/Vancomycin (n = 16, P = .003), Ceftazidime (n = 10, P = .03), or multiple systemic antibiotics (n = 53, P = .001) showed significantly lower 3-IS levels compared to mono-antibiosis with Rifaximin (n = 14) or intravenous Vancomycin (n = 4, not statistically significant). Conclusions: Different types of antibiotic treatments show different impacts on markers of microbiome diversity. The identification of antibiotics sparing commensal bacteria remains an ongoing challenge. However, Rifaximin allowed a higher intestinal microbiome diversity, even in the presence of systemic broad-spectrum antibiotics.